Polymer systems for oral delivery of insulin (Chemical Bulletin of Kazakh National University, 2023)
Diabetes mellitus is among the top ten leading causes of death worldwide and remains a serious health problem. More than half a billion people worldwide have diabetes, which occurs when the body is unable to produce insulin or due to the inefficient use of the produced insulin. To keep blood glucose levels within the acceptable norm, people with type 1 diabetes need daily injections of insulin. Even though insulin remains an indispensable drug in the treatment of diabetes, its injectable form prevents its wider use. To eliminate the barriers associated with the injectable form of insulin, improve ease of use, and supply therapeutic benefits, a lot of work is underway to create an oral form of insulin. This review is devoted to the presentation of general information about modern achievements in the creation of an oral form of insulin. The paper describes the prevalence of diabetes mellitus and its treatment, methods of protein encapsulation, difficulties in the use of oral insulin, as well as various approaches that have been taken to overcome barriers to the creation of an oral form of insulin. The latest achievements in the use of mucoadhesive polymers and hydrogels for drug delivery are considered. Mucoadhesive polymers such as chitosan and alginate are attracting increasing attention due to their properties such as pH sensitivity, biocompatibility, and biodegradability. Methods of encapsulation of protein drugs with the use of spray drying, emulsification, and deposition of polymer materials by complexation are presented.
Keywords: diabetes mellitus; insulin; encapsulation; mucoadhesive polymers; hydrogels